The effect of professional competence and organizational culture on performance english teacher - Emita, Isyana; Syamsudin; Sugeng, Irwin Sukrisno (Priviet Social Sciences Journal, 2021)
Human resources (HR) in companies need to be managed professionally to realize a balance between the needs of teachers and the demands and abilities of professional organizations. The high performance of teachers will pave the way for organizations to achieve their goals, otherwise, low teacher performance will hinder the organization in achieving its goals. Professional competence is important because with professional competence every teacher will be willing to work hard and enthusiastically to achieve higher performance. An appropriate organizational culture can support the implementation of work so that teachers have the enthusiasm to work and improve performance. This study was conducted to determine the effect of professional competence and organizational culture on the performance of English teachers at Private Junior High Schools, Pondok Gede District - Bekasi. This study uses quantitative research methods to determine the sample with a saturated sample. The sample used was 40 respondents. Methods of data analysis in this study using multiple linear regression method. The result of this study is that motivation has a significant effect on teacher performance, with the value of t table > t arithmetic (2.450) > t-table (2.026). The organizational culture variable has a significant effect on teacher performance with a t-count value (2.537) > t table (2.026). Professional competence and organizational culture have a simultaneous effect on the work environment with a calculated F value > F table (10.086 > 3.252) and a sig value with a significant level of 0.000.